2013
DOI: 10.1007/s13592-013-0199-4
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal doses of imidacloprid decreased size of hypopharyngeal glands and respiratory rhythm of honeybees in vivo

Abstract: International audienceMost studies that have shown negative sublethal effects of the pesticide imidacloprid on honeybees concern behavioral effects; only a few concern physiological effects. Therefore, we investigated sublethal effects of imidacloprid on the development of the hypopharyngeal glands (HPGs) and respiratory rhythm in honeybees fed under laboratory conditions. We introduced newly emerged honeybees into wooden mesh-sided cages and provided sugar solution and pollen pastry ad libitum. Imidacloprid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 59 publications
7
82
1
2
Order By: Relevance
“…It has recently been observed that sublethal doses of imidacloprid have a decreasing effect on hypopharyngeal glands (HPGs) of the nursing bees (Hatjina et al, 2013). The changes in the size of HPGs (which refers to the diameter of acini) constitute an indicator of the activity of HPGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been observed that sublethal doses of imidacloprid have a decreasing effect on hypopharyngeal glands (HPGs) of the nursing bees (Hatjina et al, 2013). The changes in the size of HPGs (which refers to the diameter of acini) constitute an indicator of the activity of HPGs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we can conclude that pollen containing both doses of IMD decreases the level of the honey bee proteins and it suggests an intense negative effect of the pesticide on the activity of the honey bee's HPGs. The causes of this phenomenon presumably lie in a decrease in the size of HPG lobules (Hatjina et al, 2013). This leads to a disturbed protein synthesis in the glands, and in particular to a decrease in the production of royal jelly by nurse bees (Ohashi, Natori, & Kubo, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen also represents one of the most frequent ways of exposure to pesticides (Krupke et al 2012;Mullin et al 2010), particularly relevant for nurse bees and larvae, which consume the highest amount of stored pollen (Rortais et al 2005). The residual concentrations of highly toxic pesticides, like neonicotinoids, are still able to induce adverse effects in bees, such as the lowered development of HPGs demonstrated in newly e m e rg e d b e e s c h r o n i c a l l y e x p o s e d t o imidacloprid (Hatjina et al 2013;Heylen et al 2011;Smodiš Škerl and Gregorc 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Babendreier et al 2005;Hatjina et al 2013;Heylen et al 2011;Smodiš Škerl and Gregorc 2010), little is known about combination of stressors, which can occur in a field-realistic scenario. Here, we tested the hypothesis that low protein content in pollen combined with pesticide exposure has a significant impact on young-bee development.…”
Section: Introductionmentioning
confidence: 99%